2002
DOI: 10.1039/b110213n
|View full text |Cite
|
Sign up to set email alerts
|

Human fibroblast alterations induced by low power laser irradiation at the single cell level using confocal microscopy

Abstract: Low power laser irradiation is regarded to have a significant role in triggering cellular proliferation and in treating diseases of diverse etiologies. The present work contributes to the understanding of the mechanisms of action by studying low power laser effects in human fibroblasts. Confocal laser scanning microscopy is used for irradiation and observation of the same area of interest allowing the imaging of laser effects at the single cell level and in real time. Coverslip cultures were placed in a small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
115
0
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(122 citation statements)
references
References 39 publications
(38 reference statements)
2
115
0
5
Order By: Relevance
“…A long series of discoveries have demonstrated that ATP is not only an energy currency inside cells but is also a critical signalling molecule that allows cells and tissues to communicate (Karu, 2010). Alexandratou et al (2002) found that the increased formation of ROS combined with increased intracellular Ca 2+ and mitochondrial membrane potential are mechanisms involved in necrosis following irradiation. Low doses of irradiation can stimulate increased Ca 2+ and induce mitosis increasing cellular proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…A long series of discoveries have demonstrated that ATP is not only an energy currency inside cells but is also a critical signalling molecule that allows cells and tissues to communicate (Karu, 2010). Alexandratou et al (2002) found that the increased formation of ROS combined with increased intracellular Ca 2+ and mitochondrial membrane potential are mechanisms involved in necrosis following irradiation. Low doses of irradiation can stimulate increased Ca 2+ and induce mitosis increasing cellular proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Photodamage during microscopy indeed indicates that cells can be stimulated solely by photons. Along with this idea, it was found that low energy visible light irradiation with about 0.1 mw/cm 2 power density for seconds to minutes could induce changes of intracellular Ca 2+ concentrations in macrophages [76], sperms [77][78][79], lymphocytes [80], skeletal muscle cells [81,82], human fibroblasts [83] and mast cells [84]. The cellular Ca 2+ level slowly increased during continuous laser irradiation and could maintain for minutes.…”
Section: All-optical Stimulationmentioning
confidence: 99%
“…Этот результат косвенно подтверждает высказанное ранее предположение о ведущей роли ионов каль-ция, высвобождаемых из внутриклеточных депо [9,10], которые, как известно, распространяются в виде волн с периодом 100 с (рис. 2) [12]. Для изучения активности фермента НАДФ-оксидазы в серии опытов в аналогичных условиях выделенные из крови доноров нейтрофилы подвер-гали лазерному освечиванию при температуре 37 °C, для чего в силиконизированную кювету со свето-изолированными стенками вносился 1 мл раствора Хенкса, содержащего 5×10 6 нейтрофилов в 1 мл.…”
Section: результаты и обсуждениеunclassified